Analisis Stabilitas Lereng Galian Waduk Brigif Terhadap Perbedaan Tinggi Muka Air Rencana - Avianza, Ardha Dissa; Pradiptya, Andikanoza; Agung, Putera Agung Maha (Indonesian Society of Applied Science, 2023)
Excavation is one of the works whose purpose is to adjust the existing surface height to the height of the planned surface and cause the value of the slope stability to decrease due to the loss of the natural soil retaining layer. Slope stability analysis is carried out with the aim of predicting changes in the value of safety numbers (SF) that occur as a result of excavation work. The excavations carried out are categorized as deep excavations with a depth of 8.16 m and are used terraces. Slope stability analysis using manual calculation of Simple Bishop method divided by 17 slices and application calculation using Geostudio-2012. Slope stability analysis is carried out during the service period with low-high water level conditions. The results of manual analysis at low water level conditions are predicted to have an SF value under normal conditions of 4.6 and when the condition is earthquake at 2.7. Meanwhile, the results of the analysis with the application obtained the results of predicting the SF value under normal conditions of 4.2 and in earthquake conditions of 2.6. However, analysis of high water level conditions is predicted to manually reduce the SF value of 2.5 under normal conditions and 1.6 in earthquake conditions. Then, using the application, the results of predicting the SF value at normal conditions of 2.5 and in earthquake conditions of 1.6 were obtained. In general, the stability of the slopes under review has safe conditions under normal conditions and earthquake conditions.